Cell Deposition Microchip with Micropipette Control over Liquid Interface Motion. (17th May 2018) - Onoshima, Daisuke; Hattori, Yuya; Yukawa, Hiroshi; Ishikawa, Kenji; Hori, Masaru; Baba, Yoshinobu
Positioning single cells on a solid surface is a crucial technique for understanding the cellular functions and cell–cell interactions in cell culture assays. We developed a microfluidic chip for depositing single cells in microwells using a simple micropipette operation. Cells were delivered to microwells by the meniscus motion of liquid interface. The residue deposits of cells were redistributed with air injection, and the isolated single cells were stored in microwells. Different microwell sizes and depths were studied to evaluate the trapping possibility of cells. Medium replacement and cell viability staining with the isolated single cells were achieved in microwells. The chip will serve as a tool for single-cell patterning in an easy-to-use manner.